PENGARUH MOTIVASI, PERSEPSI DAN PEMBELAJARAN TERHADAP KEPUTUSAN BERWIRAUSAHA MASYARAKAT DIKECAMATAN SEBERANG ULU I PALEMBANG - Yudha Mahrom DS; Diah Isnaini Asiati; Gumar Herudiansyah (Fakultas Ekonomi Universitas IBA, 2022)
The encouraging efforts of economic growth through the development of entrepreneurship programs continue to be done. Following this, various entrepreneurship studies are also continuously evaluated in order to optimize the results. One of these studies is to determine the effect of motivation, perception, and learning process, on community entrepreneurial decisions in Seberang Ulu II District, Palembang City, South Sumatera Province. This research is an associative type, which tries to link the variables of motivation, perception, learning process, with entrepreneurial decisions. The sample used was 100 respondents who were taken by purposive sampling. The main data used is primary data with the data collection method using a questionnaire. The analysis method in this study uses multiple linear regression analysis. The results of the hypothesis proof show that 1) there is a significant influence of motivation, perception, and learning process, on entrepreneurial decisions; 2) there is a significant influence of motivation on entrepreneurial decisions; 3) there is a significant effect of perception on entrepreneurial decisions; and 4) there is no significant effect of learning process on entrepreneurial decisions. The value of determination coefficient shows that the variables of motivation, perception, and learning process, are able to contribute to the ups and downs of entrepreneurial decisions in the amount of 7.1%.